Auditor Work Environment and Professional Judgment in Audit: Evidence from Indonesia - Trinandari Prasetya Nugrahanti; Shanti Lysandra; Hasan Ashari (Australasian Accounting, Business and Finance Journal, 2024)
Auditors must become more professional due to the nature of the work environment in auditing, which requires them to make judgments and face many dynamics that arise during the auditing process. This study aims to analyze the work environment of auditors, which affects their professional judgment when auditing financial statements. This study uses quantitative and descriptive methods with convenience sampling techniques with auditor respondents who work at the Public Accounting Firm in the DKI Jakarta Region of Indonesia. The results of this study indicate that auditor behavior, work environment, and information technology positively affect professional judgment. Auditors who behave according to their professional code of ethics will use their professional judgment better and more appropriately when providing opinions on audited financial statements. A conducive work environment will make it easier for auditors to use their professional judgment better and more correctly in decision-making. The use of information technology helps auditors complete their work appropriately and efficiently so that they can better their professional judgment.
Keywords: Audit work environment; Professional judgment audit